2008
DOI: 10.1016/j.chemosphere.2008.01.062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al(III) speciation on coagulation of highly turbid water

Abstract: In Taiwan, the turbidity of raw water for fresh water treatments can sometimes reach as high as 40 000 NTU due to intensive rainfall, especially in typhoon seasons. In response, water works often apply large quantities of coagulants such as polyaluminium chloride (PACl). In this study, simulated and natural highly turbid water was coagulated with two PACls, a commercial product (PACl-1) and a laboratory product (PACl-E). The Al species distributions of PACl-1 and PACl-E under various pH conditions were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 33 publications
3
30
0
2
Order By: Relevance
“…Under the same dosage, zeta potential was in the sequence of Al 13 > PACl > AS, which had a good correlation with the content of Al b (as shown in Table 1). This is consistent with the published literature which indicates that the active Al 13 species in the pre-hydrolyzed aluminum salts is the most highly charged [28]. It should be noted that zeta potentials for PACl and Al 13 became positive as their concentrations increased to 5.0 mg/L and above, which might lead to re-stabilization of the colloidal matters.…”
Section: Removal Of Ha With Different Al-based Coagulants/miex Resinsupporting
confidence: 92%
“…Under the same dosage, zeta potential was in the sequence of Al 13 > PACl > AS, which had a good correlation with the content of Al b (as shown in Table 1). This is consistent with the published literature which indicates that the active Al 13 species in the pre-hydrolyzed aluminum salts is the most highly charged [28]. It should be noted that zeta potentials for PACl and Al 13 became positive as their concentrations increased to 5.0 mg/L and above, which might lead to re-stabilization of the colloidal matters.…”
Section: Removal Of Ha With Different Al-based Coagulants/miex Resinsupporting
confidence: 92%
“…This could be explained by the variation of hydrolyzed Al species with pH. The PACl applied in this study contained a large fraction of monomeric Al species, which formed hydrolyzed Al(OH) 3 at neutral pH [27]. Our work also indicated that the amounts of hydrolyzed Al(OH) 3 was a critical factor in determining the coagulation mechanism [35].…”
Section: Effect Of Coagulation Mechanism On the Destabilization Of Sfmentioning
confidence: 55%
“…Researchers have also suggested that the enhancement of membrane permeability was strongly related to the strength and size distribution of the flocs [22][23][24][25][26]. For Al-based coagulation, the property of the flocs is dictated by the mechanism of coagulation induced by various hydrolyzing Al species [27]. Mechanisms of coagulation by hydrolyzing these include charge neutralization of negatively charged colloids and incorporation of impurities into an amorphous hydroxide precipitate (i.e., sweep flocculation) [28].…”
Section: Introductionmentioning
confidence: 99%
“…The initial flux at this pressure was measured to be approximately 1000 L/m 2 /d and remained constant until day 14. In Run-3, the TMP was further increased to 3.0 kPa and operated continuously for 5 days (days [15][16][17][18][19] 2 and 3), and <0.1 mg/L (except day 2), respectively, which were approximately 99.4% of the average removal from the raw SFBW. In Run-2, feed water turbidity, Fe, and Mn were measured as 319-770 NTU, 14-78.5 mg/L, and 2.4-10.15 mg/L, respectively.…”
Section: Fluxprofile With Different Tmpsmentioning
confidence: 99%
“…The consistency of the filtration flux largely depends on the size and structure of the flocculants formation, which eventually dependson the operating conditions such as pH and coagulant dosages [14][15][16]. For alum coagulation, size and structure of the flocculants are induced by various hydrolyzing Al species [17]. The application of an alum coagulant in a coagulation/microfiltration process has beeninvestigated in the recent past [18][19][20].…”
Section: Introductionmentioning
confidence: 99%